The Relationship Between Cancer and Functional and Structural Markers of Subclinical Atherosclerosis: A Systematic Review and Meta-Analysis - Diao, Yuhong; Liu, Zhixing; Chen, Li; Zhang, Weiping; Sun, Dandan (Frontiers in Cardiovascular Medicine, 2022)
Objectives: The relationship between cancer and subclinical atherosclerosis has always been the focus of people's attention. We conducted a systematic review and meta-analysis by evaluating the effects of cancer on functional and structural markers of subclinical atherosclerosis:intima-media thickness (IMT), pulse wave velocity (PWV), and flow-mediated vasodilation (FMD). Methods: A comprehensive and systematic literature search was conducted on the internet. Sensitivity analysis, publication bias, standard mean difference (SMD), corresponding 95% confidence interval (95% CI), and subgroup analysis were performed for all relevant research indicators in the retrieved literature. Results: Forty-six studies were included, including 3729 cancer patients and 2404 healthy controls. Cancer patients had significantly thicker IMT (SMD (95%CI) = 0.290 (0.069 to 0.511), P = 0.010) and higher PWV (SMD (95%CI) = 0.392 (0.136 to 0.647), P = 0.003) compared with healthy controls. There was no significant difference in FMD (SMD (95% CI) = -0.192 (-0.527 to 0.144), P＞0.05). After subgrouping by age and male proportion, the analysis results of IMT ≥ 50 years old, PWV and FMD < 50 years old, and male proportion ≥50% were statistically significant (P < 0.05). There were no significant differences in other subgroup analyses, overall sensitivity analysis, and publication bias (p＜0.05). Conclusions: Cancer may promote subclinical atherosclerosis, and change the functional and structural markers of subclinical atherosclerosis such as IMT and PWV. Early intervention and prevention should be pursued.